2017
DOI: 10.18203/2394-6040.ijcmph20174816
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of maternity care services among pregnant women in a coastal area in central Kerala, India

Abstract: Background: Maternal care services are intended to take care about the pregnant during the antenatal, intra natal and post natal periods so as to reduce maternity related health problems. The current study tries to assess maternity care services among pregnant women in a coastal area in central Kerala, India.Methods: The setting was Mararikkulam south panchayat and the study was cross sectional in nature. The minimum sample size of the study was calculated to be 213. A house to house survey was conducted in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…11 On the other hand Soman et al in their study in coastal areas of Kerala reported insufficient antenatal care services in coastal areas compared to other areas of Kerala. 12 In a state like Kerala with high human development index, there is a scope to improve antenatal care services by creating awareness among the women of reproductive age.…”
Section: Discussionmentioning
confidence: 99%
“…11 On the other hand Soman et al in their study in coastal areas of Kerala reported insufficient antenatal care services in coastal areas compared to other areas of Kerala. 12 In a state like Kerala with high human development index, there is a scope to improve antenatal care services by creating awareness among the women of reproductive age.…”
Section: Discussionmentioning
confidence: 99%
“…Terdapat pengaruh yang bermakna antara kerentanan, keseriusan, manfaat dan isyarat berpengaruh terhadap kejadian anemia pada ibu hamil di Kabupaten Kepahiang. ( Syafti, R.O et al,,2021).. Pelayanan antenatal care di daerah pesisir masih rendah dibandingkan dengan daerah lain (Soman et al, 2017). Perbedaan dengan peneitian ini adalah metode penelitian kualitaitif dengan sasaran ibu hamil dari masyarakat nelayan.…”
Section: Pendahuluanunclassified